2022
DOI: 10.1111/1467-9477.12242
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup contact reduces affective polarization but not among strong party identifiers

Abstract: Previous studies have assumed that the relationship between intergroup contact and affective polarization is uniform across political predispositions. We argue instead that party identification serves as a boundary condition for the intergroup contact‒affective polarization relationship. Our findings suggest that: (1) intergroup contact between “in‐party” and “out‐party” supporters reduces affective polarization among nonidentifiers, weak, and moderate party identifiers, and (2) intergroup contact remains unre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Research on positive emotions and political behavior has been less common, but given that affective polarization is based in social identity theory, a theoretical point of departure will be to explore how positive intergroup contact may reduce affective polarization as postulated by the contact hypothesis (Allport, 1954). Recent research by Thomsen and Thomsen (2022) shows that intergroup contact does seem to reduce affective polarization. Similarly, Borinca et al (2022) show that imagining positive contact with an outgroup influences intergroup support and positive emotions, and that these effects were magnified among those who most opposed the outgroups from the start.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Research on positive emotions and political behavior has been less common, but given that affective polarization is based in social identity theory, a theoretical point of departure will be to explore how positive intergroup contact may reduce affective polarization as postulated by the contact hypothesis (Allport, 1954). Recent research by Thomsen and Thomsen (2022) shows that intergroup contact does seem to reduce affective polarization. Similarly, Borinca et al (2022) show that imagining positive contact with an outgroup influences intergroup support and positive emotions, and that these effects were magnified among those who most opposed the outgroups from the start.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…There is no room to review all the proposed strategies and analyses of their effectiveness. A sample of the recent literature is given by: [ 24 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. The evidence is mixed, in that some depolarizing methods work in some environments, but fail in others.…”
Section: Social Sciences and Opinion Modeling Backgroundmentioning
confidence: 99%
“…This triggers favourable behavior towards the ingroup and unfavourable behavior towards the outgroup (Hogg, CooperShaw, and Holzworth 1993;Dovidio et al 2012). Following this motivational component in the self-categorization process, greater differences in relation to members of other groups might block any attempt of extending ingroup favourableness to them (Thomsen and Thomsen 2022). Stuart Turnbull-Dugarte and Alberto López (2023) recently found that citizens are willing to even change preferences over important issues associated to the ingroup identity if this avoids the reduction of identity-based distinctiveness concerning the outgroup.…”
Section: Self-identification With the Ingroup And Social Recategoriza...mentioning
confidence: 99%